I Cannot Miss It for the World: The Relationship Between Fear of Missing out (FOMO) and Acceptance of ChatGPT - Li, Heng (Basic and applied social psychology, 2024)
According to the technology acceptance model, people's acceptance of new technology is influenced by their perception of its usefulness and ease of use. We expand the research agenda by identifying the fear of missing out (FOMO) as a potential factor shaping people's attitudes toward ChatGPT. We predicted that FOMO experiences, characterized by strong desires to stay connected with other people's lives, would be linked to more AI-related supportive attitudes. In Study 1 (N = 209), university students with more frequent experiences of FOMO showed more favorable attitudes toward ChatGPT. Study 2 (N = 126) found that participants with a greater FOMO were more likely to choose an invitation letter purportedly authored by ChatGPT, despite it being composed by a human, which provided a behavioral choice confirmation of the observed relationship. Study 3 (N = 186) replicated the findings in a tourism context by employing non-student populations. Study 4 (N = 150) explored the propensity for participants to engage with ChatGPT in personal music selection process and obtained the same effect. Together, these findings suggest that the FOMO bias may exert an additional influence on the endorsement of new technologies, which highlights the important role of emotion in technology acceptance.